Upaya Meningkatkan Keaktifan dan Hasil Belajar Matematika Materi Perkalian dan Pembagian melalui Metode Demonstrasi dengan Media Tali PAS pada Siswa Kelas II Semester Genap Sekolah Dasar Negeri Gentan 03 Kecamatan Bendosari Kabupaten Sukoharjo Tahun Pelaj - Chaeroh, Miratu; Rahma Rista Utami, Novia; Jumini, Sri (Social Science Academic, 2023)
This study aims to improve student activeness and learning outcomes in mathematics subjects, especially multiplication and division materials, by applying a demonstration method using PAS rope media in grade II SD Negeri Gentan 03, Bendosari District, Sukoharjo Regency. Classroom action research methods are used with several cycles that include planning, action execution, observation, and reflection. Data was collected through observation of student activity, test results, and observation of teacher activity. Before the action was taken, student activity was moderate with an active level of 50%. After the application of the demonstration method with PAS rope media, there was a significant increase in student activity. In cycle I, the level of activity increased to 61% (medium category), in cycle II it increased to 74% (medium category), and in cycle III it increased to 94% (high category). Student learning outcomes before the action showed that 61% of students were incomplete, and 39% of students were complete (low category). However, after conducting research with demonstration methods and PAS rope media, there was an increase in learning outcomes. In cycle I, incomplete students decreased to 39%, and completed students increased to 61% (medium category). In cycle II, incomplete students decreased to 29%, and completed students increased to 71% (medium category). In cycle III, there was a significant increase with only 7% of students who had not completed, and 93% of students completed (high category).